Barely legal [large type] - Woods, Stuart; Hall, Parnell (Woods, Stuart. Herbie Fisher novel, 2017)
Under the tutelage of Stone Barrington, Herbie Fisher has transformed from a bumbling sad sack into a capable man-about-town and the youngest senior partner at the white-shoe law firm Woodman & Weld. Now all of his training will be put to the test as he finds himself embroiled in his most daring adventure to date and which -- unbeknownst to him -- has put him at the center of a bull's-eye. In the city that never sleeps there are always devious schemes afoot, and Herbie will have to be quick on his feet to stay one step ahead of his enemies... and they're closing in.